Gastrointestinal and Cardiovascular Effects of Shiftwork in Nurses - Narges Kaydani; Kourosh Zarea; Ahmad Soltanzadeh (Shiraz University of Medical Sciences, 2023)
Background: Gastrointestinal and cardiovascular diseases are considered to be among the consequences of shiftwork in nursing staff. This study aimed to investigate the prevalence of gastrointestinal and cardiovascular diseases and model their consequences in nurses.Methods: This cross-sectional study was conducted in seven hospitals in Khuzestan Province in 2020. The participants of the study were 652 nurses. The data were collected through a questionnaire developed by Choobineh et al. The questionnaire included demographic questions and shift work related health effects. The modeling was performed via logistic regression in SPSS 22.Results: The prevalence of gastrointestinal (52.53% vs. 35.19%) and cardiovascular (35.02% vs. 22.22%) disorders were significantly higher in shift working nurses than in day-working ones (P<0.05). In addition to shiftwork, work experience, working hours per week, and hospital wards significantly affected the prevalence of gastrointestinal disorders in nurses (P<0.05). The shiftwork system, age, work experience, and working hours per week had significant positive correlations with the prevalence of cardiovascular diseases in nurses (P<0.05). Furthermore, the chance of having gastrointestinal and cardiovascular diseases was 2.73 and 2.08 times more in shift-working nurses than in day-working ones, respectively.Conclusion: Beside the shift work, the findings of the study indicated the important role of other risk factors, such as age, work experience, working hours per week, and hospital wards for the prevalence of gastrointestinal and cardiovascular diseases in nurses. Therefore, it is recommended that these factors should be taken into account while trying to manage, control, and reduce such negative consequences in nurses.